Air Drag Charging for Electric Vehicles - Joy, Alexander; Pathrose, Jais; Paul Kandathil, Rony; Thomas, Eldho; Kappillil, Nidheesh (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Aerodynamic Drag is the resistance offered by the air to the movement of the body. In our project we are trying to utilize air drag to charge electric vehicles. This is achieved by creating a charging mechanism which gets activated when the electric vehicle apply brake to stop or slow down. Aerodynamic Drag creates a large amount of force on vehicles. Placement of a turbine in the front area of the car could generate electricity from the drag force. But when we place turbine in front of the vehicle it will create additional drag. But at the time of braking the drag is actually assisting the breaking process. At the time of breaking we could utilize this drag force to generate electricity. Here the additional drag created will help the breaking process.
Keywords: Aerodynamic drag; turbine; breaking